EXPLORING SECONDARY EFL STUDENTS' MOTIVATIONAL BELIEFS OF SELF-REGULATED LEARNING THROUGH TEACHER’S SPEAKING TASK - Prihandy, Radenal; Sumarta, Sumarta; Abas, Totoh Tauhidin (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to find out students' motivational beliefs in doing speaking tasks. The participants were six 11th graders in Jakarta who were categorized by low and high speaking proficiency. This study collected data from the Motivated Strategies for Learning Questionnaire (MSLQ) interview. The researcher adapted semi-structured interviews based on the indicators of MSLQ. The results showed students’ motivational beliefs that Low-proficient students obviously have less motivational beliefs oriented on score values as their motivation, and high-proficient students have high motivational beliefs oriented on their ability to progress to their future goal orientation. These motivational beliefs demonstrated the importance of goal orientation in encouraging learners' motivation and the promotion of the important use of motivational beliefs on students in doing teacher-speaking tasks.